Hierarchical approach to Vehicle Routing and Scheduling - Kim, Kyoung C; Sun, Ji U; Lee, Shi W (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
To survive in today’s competitive market, material handling activities need to be planned carefully to satisfy business’ and customers' demand. The vehicle routing and scheduling problems have been studied extensively for various industries with special needs. In this paper, a vehicle routing problem considering unique characteristics of the electronics industry is considered. A mixed-integer nonlinear programming (MINP) model has been presented to minimize the traveling time of delivery and installation vehicles. A hierarchical approach using the genetic algorithm has been proposed and implemented to solve problems of various sizes. The computational results show the effectiveness and the efficiency of the proposed hierarchical approach. A performance comparison between the MINP approach and the hierarchical approach is also presented.